Pengaruh Pemberian Sari Buah Mengkudu (Morinda citrifolia Linn.) Terhadap Glibenklamid dalam Menurunkan Kadar Glukosa Darah Tikus Putih Jantan yang Dibuat Diabetes - Sari, Santi Purna; Munim, Abdul; Fitriani, Sri Wulandah (UI Scholars Hub, 2012)
Drug interactions can occur in the use of two or more drugs simultaneously, including the use of synthetic drug with herbal medicine. Combination of glibenclamide with noni juice (Morinda citrifolia Linn.) often used by diabetic patient to decrease their blood glucose level. lhe aim of this research was to know the interaction between glibenclamide and noni juice administration on blood glucose level. This research used 24 Sprague-Dawley male rats which were divided into 6 groups. Before the experiment, the rats were first induced by alloxan, except group 1, which was the normal control. Group 2 was the control of diabetic without given any drugs. Group 3 and 4 were the control of glibenclamide (0.9 mg/200g body weight of rat) and of noni juice (2.5 ml/200g body weight of rat) respectively. Group 5 and 6 were the interaction test group which were given glibenclamide (0.9 mg/ 200 g body weight rat) and noni juice (2.5 ml or 5.0 ml/200 g body weight of rat) with an hour interval. The blood glucose level was measured by using spectrophotometer with o-toluidine as reagent. The result of this research shows that noni juice at a dose 5.0 ml/200 g body weight rat was able to increased the reduction of blood glucose levels by glibenclamide after two weeks administration